Neural changes underlying successful second language word learning: An fMRI study - Yang, Jing; Gates, Kathleen Marie; Molenaar, Peter; Li, Ping (Journal of neurolinguistics, 2015)
A great deal of research has examined behavioral performance changes associated with second language learning. But what changes are taking place in the brain as learning progresses? How can we identify differences in brain changes that reflect successes of learning? To answer these questions, we conducted a functional magnetic resonance imaging (fMRI) study to examine the neural activities associated with second language word learning. Participants were 39 native English speakers who had no prior knowledge of Chinese or other tonal language, and were trained to learn a novel tonal vocabulary in a six-week training session. Functional MRI scans as well as behavioral performances were obtained from these learners at two different times (pre- and post-training). We performed region of interest (ROI) and connectivity analyses to identify effective connectivity changes associated with success in second language word learning. We compared a learner group with a control group, and also examined the differences between successful learners and less successful learners within the learner group across the two time points. Our results indicated that (1) after training, learners and non-learners rely on different patterns of brain networks to process tonal and lexical information of target L2 words; (2) within the learner group, successful learners compared to less successful learners showed significant differences in language-related regions; and (3) successful learners compared to less successful learners showed a more coherent and integrated multi-path brain network. These results suggest that second language experience shapes neural changes in short-term training, and that analyses of these neural changes also reflect individual differences in learning success. •We examine different neural activity and connectivity patterns associated with success in second language word learning.•After training on novel words, learners compared to non-learners showed different neural response changes in semantic and auditory processing.•After training, successful learners compared to less successful learners showed increased activation in language-related regions.•Successful learners showed a more coherent and integrated multi-path brain network both before and after training.